Polyelectrolyte–protein complexes - Cooper, C.L.; Dubin, P.L.; Kayitmazer, A.B.; Turksen, S. (Current opinion in colloid & interface science, 2005)
The field of polyelectrolye–protein complexes is now benefiting from the convergence of three themes whose disciplinary distinctions formerly produced fragmentation. Theory and simulations, previously restricted to isotropic models of colloids and polyelectrolytes, are now taking into account the heterogeneity of charges in both macroions and providing far more realistic depictions of proteins. Applications of protein–polyelectrolyte systems have been strongly influenced by the opportunities presented by multilayer assembly, and the dichotomy between semi-synthetic systems and the protein–biopolyelectrolyte cognate pairs of biochemical interest has been giving way to less parochial recognition of universal effects. The junction of these disciplines, along with the development of many new methods of investigation, form the subject of this review focused on recent developments and their foundations.